Nicaragua : Ex-Post Impact Evaluation of the Emergency Social Investment Fund - World Bank (Washington, DC, 2013)
The Emergency Social Investment Fund (FISE) ex-post impact evaluation, is one of the first to be carried out on a social fund since the introduction of these mechanisms, a decade ago. Through strong impact evaluation methodologies, the report provides empirical evidence regarding FISE's success in reaching poor households, and contributing to their human capital formation, and provides as well, insights into communities interactions with FISE, and the quality of publicly provided social services that have received a FISE investment. The evaluation makes use of data sources, such as the Living Standards Measurement Survey (LSMS), FISE Household Surveys, and FISE Facilities Survey, as well as from the qualitative beneficiary assessment, instruments which allow an integrated evaluation on assessment of poverty targeting, and household impact. Based on social sectors results, recommendations for FISE operations, its work with others, and its monitoring system, suggest increased community participation at the subproject level, including a revision on the balance between social sector infrastructure investments, and, replacement, rehabilitation, and expansion of existing infrastructure. FISE's coordination with other institutions should be strengthened, to forge stronger community links, and, to balance decentralization, and strategic planning, while complementing infrastructure supply, with demand-side interventions, through direct household contacts. Finally, the link between LSMS and the FISE evaluation should be maintained, to compare alternative interventions, strengthening monitoring and evaluation activities.